Environmental risk assessment of explosive residues toxicological impact on humans on the former combat area - Orel, Serhiy; Durach, Vadim; Naumko, Mykhaylo (Видавництво Львівської політехніки, 2022)
This article evaluates the impact of explosives residues left after the explosion of low-detonation munitions on the health of population (children and adults) living on the former battlefield. To determine the toxicological impact of explosives on humans, we used data from artillery shelling near the village of Stepanivka, Donetsk region, during the fighting in 2014. By the number of craters formed on the battlefield and their size, the calibre of the shells and, accordingly, the mass of the explosives were determined. When calculating the mass of unexploded explosives, it was assumed that the number of munitions with low detonation was 2.5 %, while the mass of “unburned” explosives in them was 37 % from the total. The types of explosives were mixtures of 2, 4, 6-trinitrotoluene (TNT) – 40 % and 1, 3, 5-trinitro-1, 3, 5-triazacyclohexane (RDX) – 60 %. To assess the toxicological effects of explosives on humans, this study used the EPA's assessment model of health risk. Noncarcinogenic and carcinogenic risks associated with the influence of explosives on people were evaluated. The results of the risk assessment suggest that the residual amount of explosives in the soil does not lead to dangerous consequences for the health of people who are living on the territory of the former hostilities. However, the lack of data about the location of explosive objects (unexploded munitions, land mines etc.) into the soil of Donbas does not allow us fully assess their toxicological hazard to humans and the environment. The problem of the toxicological impact of explosive residues on residents and the environment of the Donbas region remains relevant.
Keywords: risk assessment; toxicological impact; explosives; low detonation